A dual mediation model approach to evaluating the persuasiveness of wine destination websites - Quintal, Vanessa; Phau, I. (Croatian National Tourist Board, 2017)
This study utilized dual mediation theory to investigate the persuasiveness of wine destination management organizations' (DMO) websites in influencing user cognition, attitude, and behavioral intention. Data were collected from a wine DMO's database in Australia. Website usability had significant effects on website cognition as well as cognition of wine destination setting and wine products. Cognition of wine destination maps, settings, and wine products produced significant effects on attitude toward wine destination. In turn, attitude toward wine destination influenced further information search and intention to attend wine destination events. These findings will help DMOs to identify critical website and wine destination attributes that users seek to make informed decisions.